SELF-PROTECTED COMMUNITIES TOWARDS RELATIONAL COMMUNITIES: An Appraisal of Relational-Ethical Model for Social Concern - Zhengcan Huang and Enguo Wang (Journal of Dharma, 2024)
The world is endowed with people who have plethora of talents and capabilities. This research pinpoints the relational-ethical theory concerning social and religious life of humans as well as their horizontal and vertical relations. It delves into the intricacies of relations, focusing on marital issues, women's rights, gender-based violence, and similar concerns. Simultaneously, it dismantles the mindset that seeks to transform the world into a Christendom driven by self-interest. The study draws on C. S. Song and Denise M. Ackermann's frameworks to envision the role of relational-ethical communities, challenging the narrow perspectives prevalent in today's world. Consequently, the research adopts the relational-ethical model to showcase its broader aspect, breaking down individualism and employing analogies from St. Paul to advocate for a more just world.